2014
DOI: 10.1140/epjc/s10052-014-3163-1
|View full text |Cite
|
Sign up to set email alerts
|

Fastlim: a fast LHC limit calculator

Abstract: Fastlim is a tool to calculate conservative limits on extensions of the Standard Model from direct LHC searches without performing any Monte Carlo event generation. The program reconstructs the visible cross sections (cross sections after event selection cuts) from pre-calculated efficiency tables and cross section tables for simplified event topologies. As a proof of concept of the approach, we have implemented searches relevant for supersymmetric models with R-parity conservation. Fastlim takes the spectrum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 101 publications
0
95
0
Order By: Relevance
“…In particular, the efficiencies of object reconstruction and the parameters associated with the momentum smearing are implemented in the form of analytical functions or numerical grids. The program has already been used in several studies [101][102][103][104], and the validation of the code can be found in [105].…”
Section: Lhc Constraints On Sparticle Massesmentioning
confidence: 99%
“…In particular, the efficiencies of object reconstruction and the parameters associated with the momentum smearing are implemented in the form of analytical functions or numerical grids. The program has already been used in several studies [101][102][103][104], and the validation of the code can be found in [105].…”
Section: Lhc Constraints On Sparticle Massesmentioning
confidence: 99%
“…Therefore the non-SM nature of the Higgs production can be revealed by looking at the boosted production. Moreover, this can make light stops [85][86][87][88][89][90][91][92][93][94][95][96][97][98] accessible which are hidden in the stealth region and challenging to extract given the similarity to the top background [99][100][101][102][103]. An outline showing this sensitivity and taking vacuum stability constraints into account has been presented in [45].…”
Section: Supersymmetrymentioning
confidence: 99%
“…We implement the CMS simplified model searches with ∼ 36/fb of data at 13 TeV for events with jets and / E T but no leptons [105] and for events with jets, / E T and a single lepton [106], using the Fastlim approach [133]. We use [105] …”
Section: Searches For Gluinos and Squarksmentioning
confidence: 99%